Lithium triborate coated lithium manganate positive electrode material and preparation method thereof

By building a porous structure on the lithium manganate positive electrode material and covering the lithium triborate layer, the structural stability and manganese dissolution of the material under high temperature and high magnification conditions are solved, and a longer cycle life and better magnification performance are achieved.

CN119812292AActive Publication Date: 2025-04-11山东诺迅新能源有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510302118.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-11
Estimated Expiration
2045-03-14

AI Technical Summary

Technical Problem

Lithium manganate positive electrode material has poor crystal structure stability and manganese dissolution problems under high temperature, high rate charge and discharge or long cycle conditions, which affects the cycle life and safety of the battery.

Method used

The porous lithium manganate/lithium triborate composite electrode material is designed to optimize the structural integrity and anti-dissolution ability of the material by building a highly connected oriented columnar pore structure and forming a dense lithium triborate coating on its surface.

Benefits of technology

It significantly improves the crystal structure stability and anti-manganese dissolution performance of the positive electrode material, extends the cycle life, improves the rate performance, and ensures the high stability and low solubility of the battery under complex operating conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812292A_ABST
    Figure CN119812292A_ABST
Patent Text Reader

Abstract

The invention relates to the field of battery materials, and provides a lithium triborate coated lithium manganate positive electrode material and a preparation method thereof. The positive electrode material is a porous lithium manganate / lithium triborate composite electrode material and comprises porous lithium manganate with a high-connectivity oriented columnar pore structure and a lithium triborate coating coated on the pore surface, the mass ratio of the porous lithium manganate to the lithium triborate coating is (86.0-92.0): (8.0-14.0), the thickness of the coating is 600-800 nm, the pore diameter is 45-95 microns, and the porosity is 65-78%. The preparation method comprises the following steps: preparing a precursor colloidal solution through a sol-gel method, performing low-temperature freezing forming and freeze drying to obtain porous lithium manganate, and performing pre-oxidation and high-temperature sintering to form a positive electrode substrate; and then promoting permeation of the lithium triborate precursor solution by adopting vacuum-assisted impregnation, ultrasound and nitrogen pressure, and carrying out gradient drying and annealing treatment to form a uniform coating layer. The crystal structure stability of the positive electrode material is remarkably improved, manganese dissolution is inhibited, the cycle life is prolonged, the rate capability is improved, and the positive electrode material has wide application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrode materials, and in particular to a lithium triborate-coated lithium manganate positive electrode material and a preparation method thereof. Background Art

[0002] In the context of the rapid development of lithium-ion batteries, the performance of cathode materials directly determines the energy density, cycle life and safety of batteries. Lithium manganese oxide (LiMn2O4) has broad application prospects in portable electronic devices, electric vehicles and energy storage systems due to its low cost, environmental friendliness and high specific capacity. However, in practical applications, especially under high temperature, high rate charge and discharge or long cycle conditions, the structural stability of cathode materials and the problem of manganese dissolution have become key factors affecting battery performance. The stability of the crystal structure is directly related to whether the material can maintain a complete three-dimensional framework structure during the charge and discharge process to ensure the reversible insertion and extraction of lithium ions and long-term cycle stability. At the same time, the problem of manganese dissolution not only leads to the loss of active materials and reduces the capacity retention rate of the cathode material, but also may induce side reactions at the negative electrode interface, affecting the overall safety and reliability of the battery. Therefore, in order to further enhance the practical application value of lithium manganese oxide cathode materials, it is urgent to improve its crystal structure stability and inhibit manganese dissolution through material modification strategies to ensure that the battery can still achieve excellent cycle life and stable output performance under complex working conditions. This will not only help improve the overall performance of lithium-ion batteries, but will also promote the development of new high-performance lithium battery technology and broaden its application in new energy vehicles, large-scale energy storage systems and other fields.

[0003] At present, researchers have carried out a series of modification studies on the shortcomings of lithium manganese oxide positive electrode materials in high temperature cycle stability and manganese dissolution. For example, the Chinese patent with publication number CN118908285A discloses a lithium iron manganese phosphate coated lithium manganese oxide positive electrode material and its preparation method, but lithium manganese oxide does not adopt any special structural design, so there is a problem of poor crystal structure stability during actual use. Therefore, it is urgent to develop a more stable and efficient coating strategy to improve the structural integrity and anti-dissolution ability of the material. In this context, the use of lithium triborate as a coating layer has become a promising modification scheme. Lithium triborate can not only form a dense protective layer on the surface to reduce the erosion of lithium manganese oxide by the electrolyte, but also its good ionic conductivity can ensure the smooth transmission of lithium ions, thereby improving the stability of the material while taking into account the electrochemical performance. Therefore, how to achieve a uniform, stable and efficient protective layer structure by optimizing the lithium triborate coating process to effectively improve the cycle stability and high temperature resistance of lithium manganese oxide positive electrode materials is still the focus and challenge of current research. Summary of the invention

[0004] (1) Technical issues solved The purpose of the present invention is to provide a lithium triborate coated lithium manganate positive electrode material and a preparation method thereof, so as to solve the problems of poor crystal structure stability and manganese dissolution in current positive electrode materials.

[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: Lithium triborate coated lithium manganate positive electrode material; the positive electrode material is a porous lithium manganate / lithium triborate composite electrode material; The porous lithium manganate / lithium triborate composite electrode material comprises porous lithium manganate and a lithium triborate coating coated on the pore surface of the porous lithium manganate; The mass ratio of the porous lithium manganese oxide to lithium triborate is (86.0-92.0): (8.0-14.0); The porous lithium manganese oxide is a highly connected directional columnar pore structure; The average diameter of the columnar pores of the porous lithium manganese oxide is 45-95 μm; The porosity of the porous lithium manganese oxide is 65-78%; The thickness of the lithium triborate coating is 600-800 nm.

[0006] The present invention adopts the design of porous lithium manganese oxide / lithium triborate composite electrode material, which is mainly used to enhance the crystal structure stability and manganese dissolution resistance of lithium ion battery positive electrode material. By constructing a highly connected directional columnar pore structure, the porous lithium manganese oxide ensures the efficient transmission of lithium ions while providing excellent electrochemical activity, and optimizes the structural integrity of the electrode material. Its higher porosity not only increases the specific surface area of ​​the material, improves the wettability of the electrolyte, but also effectively alleviates the material pulverization problem caused by volume change during charging and discharging, thereby enhancing the cycle stability. On this basis, the lithium triborate coating coated on the surface of the porous lithium manganese oxide pores further plays a key role. Its dense and uniform covering layer can effectively block the direct erosion of the electrolyte on lithium manganese oxide, reduce the occurrence of interfacial side reactions, and thus inhibit manganese dissolution. In addition, the presence of the lithium triborate coating helps to regulate the interfacial electric field distribution and optimize the migration path of lithium ions in the electrode material, so that the battery can still maintain excellent stability under long cycle and high rate conditions. By rationally controlling the mass ratio of porous lithium manganese oxide to lithium triborate, it is ensured that while the material improves stability, the transmission efficiency of lithium ions will not be affected by the excessive thickness of the coating layer, thereby achieving a good balance between cycle life and rate performance. Overall, the synergistic structure constructed by the present invention not only gives full play to the efficient transmission characteristics of porous lithium manganese oxide, but also utilizes the protective effect of lithium triborate, realizes the high stability and low solubility of the positive electrode material under complex working conditions, and provides reliable technical support for the long life and high safety application of lithium ion batteries.

[0007] The present invention also discloses a method for preparing a lithium triborate-coated lithium manganate positive electrode material, comprising the following steps: S1. dissolving lithium acetate and manganese acetate in anhydrous ethanol to form a metal salt solution, adding an acetone solution of polymethyl methacrylate, and stirring to obtain a precursor colloidal solution; injecting the colloidal solution into a pre-cooled mold to freeze-form, and preparing porous lithium manganate by freeze drying, pre-oxidation and high-temperature sintering; S2. The lithium triborate precursor solution is infiltrated into the pores of the porous substrate by vacuum-assisted impregnation, and then subjected to gradient drying and annealing to form a lithium triborate-coated composite positive electrode material.

[0008] Further, the preparation method of the precursor colloidal solution in step S1 is as follows: in parts by weight, 100 parts by weight of lithium acetate and 190-200 parts by weight of manganese acetate are dissolved in anhydrous ethanol, and the volume of ethanol and the mass ratio of the total metal salt are controlled to be 10-20 mL / g; under a nitrogen atmosphere, the oxygen content is controlled to be ≤50 ppm, and the mixture is continuously mixed at a mechanical stirring rate of 300-500 rpm for 20-30 min to form a uniform and transparent metal salt ethanol solution; then 30-45 parts of a 3.0-5.0 wt.% polymethyl methacrylate acetone solution are dropwise added to the above-mentioned metal salt ethanol solution at a rate of 1.0-2.0 mL / min, and the system temperature is controlled to be maintained at 20-25° C. during the dropwise addition process, and after the dropwise addition is completed, stirring is continued at a rate of 200-300 rpm for 40-60 min to obtain a dispersed and stable precursor colloidal solution; Furthermore, the freeze-forming and freeze-drying steps in step S1 are as follows: injecting the precursor colloidal solution into a metal copper mold precooled to -50~-40°C, wherein the microchannel width of the mold is 50~100μm and the depth is 200~300μm, and the inner surface is pre-coated with a polytetrafluoroethylene emulsion with a solid content of 10~15wt%, the coating thickness is 10~20μm, and the microchannel spacing is 1.0~2.0mm; gradient freezing is performed at a cooling rate of 2~3°C / min to form a frozen body with a directional pore structure; then the frozen body is transferred to a freeze dryer, and solvent sublimation is performed for 24~36h under the conditions of vacuum degree ≤5Pa and cold trap temperature ≤-85°C, and the residual solvent content is ≤0.5wt%, to obtain a dry body.

[0009] Further, the steps of pre-oxidation and high-temperature sintering in step S1 are as follows: then the dried green body is placed in a muffle furnace, the flow rate is controlled to 1~2L / min in an air atmosphere, and the temperature is heated to 350~380°C at a heating rate of 3~5°C / min, and the temperature is kept for 2.0~2.5h to complete the decomposition of the pore-forming agent and the oxidation of the precursor, and then the pre-oxidized green body is placed in an alumina crucible, the flow rate is controlled to 1.0~1.5L / min in a flowing air atmosphere, and the temperature is increased to 700~720°C at a heating rate of 5~6°C / min, and the temperature is kept for 2~4h; after sintering, it is slowly cooled to room temperature at a rate of 5~8°C / min to obtain porous lithium manganate.

[0010] Furthermore, the preparation method of the lithium triborate precursor solution in step S2 is as follows: dissolve boric acid and lithium hydroxide in deionized water in a molar ratio of 1: (0.33-0.35), adjust the pH of the solution to 6.5-7.5, and control the total boron ion concentration to 0.5-1.5 mol / L; stir at 200-400 rpm for 30-60 min at 25-40° C. to form a transparent and homogeneous lithium triborate precursor solution.

[0011] Furthermore, the impregnation process in step S2 is as follows: immersing the porous lithium manganese oxide in step S1 into the lithium triborate precursor solution, maintaining it at a vacuum degree of 10~30kPa for 10~30min to achieve sufficient penetration of the solution into the pores; then applying ultrasonic treatment, setting the frequency to 20~40kHz, the power to 50~150W, and the time to 10~30min, and then using nitrogen pressure impregnation with a pressure of 0.5~1.0 MPa and a pressurization time of 10~15min to promote uniform distribution of the sol; after the impregnation is completed, 0.5~1.0MPa nitrogen is used to purge residual droplets on the surface to ensure that there is no excess solution accumulation in the pores.

[0012] Furthermore, the gradient drying process in step S2 includes: placing the impregnated material in a program-controlled temperature drying oven and drying it in three stages: the first stage is drying at 25-40°C and humidity 30-50%RH for 1-2 hours; the second stage is drying at 60-80°C and humidity ≤10%RH for 2-4 hours; the third stage is drying at 100-120°C and vacuum ≤1kPa for 1-2 hours to complete the dehydration and pre-crystallization of the precursor.

[0013] Furthermore, the annealing treatment in step S2 includes: placing the dried material in a tubular furnace and annealing in a nitrogen-oxygen mixed atmosphere, wherein the volume ratio of nitrogen to oxygen is (93~97):(3~7); the flow rate is 0.5~1.5L / min, heating to 300~400°C at 2~5°C / min and keeping warm for 1~2h; continuing to heat to 400~500°C at 3~8°C / min and keeping warm for 3~5h; finally cooling to room temperature at 2~10°C / min to obtain a lithium triborate-coated lithium manganate positive electrode material.

[0014] The present invention adopts the design of lithium triborate coated porous lithium manganate, which is mainly used to enhance the crystal structure stability and anti-manganese dissolution performance of lithium ion battery positive electrode materials. Through a reasonable preparation method, a porous lithium manganate substrate with a highly connected directional pore structure is constructed, and a uniform lithium triborate coating layer is formed on its surface to achieve the optimization of the overall performance of the material. First, in the S1 step, a stable precursor colloid solution is formed by dissolving lithium acetate and manganese acetate in anhydrous ethanol, combined with an acetone solution of polymethyl methacrylate, to ensure the uniform dispersion of metal salts. Subsequently, freeze molding and freeze drying techniques are adopted to form a frozen blank with a directional columnar pore structure, thereby providing an excellent ion transport channel, and by pre-oxidation and high-temperature sintering treatment, a porous lithium manganate with high structural stability is obtained. Secondly, in the S2 step, a vacuum-assisted impregnation method is adopted to uniformly infiltrate the lithium triborate precursor solution into the material pores, and ultrasonic treatment and nitrogen pressure impregnation techniques are combined to further promote the uniform distribution of the sol, ensuring the integrity and stability of the coating layer. The gradient drying process uses a multi-stage temperature control strategy to gradually dehydrate and pre-crystallize the lithium triborate precursor, avoiding structural defects caused by violent solvent volatilization. It is then annealed in a nitrogen-oxygen mixed atmosphere to give the lithium triborate coating good crystallinity and chemical stability, thereby effectively inhibiting the corrosion of the electrolyte on lithium manganese oxide and reducing the occurrence of interfacial side reactions. Overall, this method allows the porous lithium manganese oxide and the lithium triborate coating to work synergistically through the fine regulation of the material structure, while improving the material cycle life, optimizing the transmission efficiency of lithium ions, achieving a balance between high rate performance and long cycle stability, and providing an effective solution for the optimized design of lithium-ion battery positive electrode materials.

[0015] (3) Beneficial technical effects 1. The present invention significantly improves the crystal structure stability and manganese dissolution resistance of the positive electrode material through the synergistic effect of porous lithium manganese oxide and lithium triborate coating. Compared with traditional materials, the cycle life is longer and the rate performance is better. The highly connected directional pore structure optimizes the lithium ion transmission path and reduces the polarization effect, while the dense and uniform lithium triborate coating effectively inhibits electrolyte corrosion and reduces interface side reactions. Reasonable component ratio, vacuum-assisted impregnation and gradient drying process ensure that the coating is uniform and stable, and optimizes the performance balance of the material under high temperature and high rate charge and discharge conditions. This technology breaks through the limitations of traditional modification methods, provides a reliable solution for high-safety, long-life lithium-ion batteries, and has broad industrial prospects.

[0016] 2. The present invention significantly improves the crystal structure stability and manganese dissolution resistance of the positive electrode material through the collaborative design of lithium triborate coated porous lithium manganate, and has better cycle life and rate performance than traditional lithium manganate positive electrode materials. The highly connected directional pore structure optimizes the lithium ion transport path and reduces the polarization effect, while the lithium triborate coating effectively inhibits electrolyte corrosion and reduces interfacial side reactions. The synergistic effect of vacuum-assisted impregnation, ultrasound and nitrogen pressure ensures that the coating layer is uniform and dense, and the gradient drying and annealing process further enhances the chemical stability of the material. Reasonable component ratios and balanced structural design avoid the adverse effects of excessively thick coating layers on ion transport while improving performance, so that the material can still maintain stable operation under high temperature and high rate charge and discharge conditions. This technical solution breaks through the limitations of traditional modification methods, provides a high-safety, long-life solution for lithium-ion batteries, and has broad prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a morphology diagram of the porous lithium manganese oxide prepared in Example 1 of the present invention.

[0018] Figure 2 This is a morphology diagram of the lithium triborate-coated lithium manganate positive electrode material prepared in Example 1 of the present invention.

[0019] Figure 3 This is a cross-sectional microstructure morphology of the lithium triborate-coated lithium manganate positive electrode material prepared in Example 1 of the present invention.

[0020] Figure 4 This is the XRD phase analysis diagram of the porous lithium manganate and lithium triborate-coated lithium manganate positive electrode materials prepared in Example 1 of the present invention.

[0021] Figure 5 This is a cross-sectional microstructure morphology of the lithium triborate-coated lithium manganate positive electrode material prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0022] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0023] Example 1 Lithium triborate coated lithium manganate positive electrode material; the positive electrode material is a porous lithium manganate / lithium triborate composite electrode material; the porous lithium manganate / lithium triborate composite electrode material includes porous lithium manganate and a lithium triborate coating coated on the pore surface of the porous lithium manganate; the mass ratio of porous lithium manganate to lithium triborate is 86.0:14.0; the porous lithium manganate has a highly connected directional columnar pore structure; the average diameter of the columnar pores of the porous lithium manganate is 45μm; the porosity of the porous lithium manganate is 65%; the thickness of the lithium triborate coating is 600nm.

[0024] A method for preparing a lithium triborate-coated lithium manganate positive electrode material in this embodiment comprises the following steps: S1. Dissolve lithium acetate and manganese acetate in anhydrous ethanol to form a metal salt solution, add an acetone solution of polymethyl methacrylate, and obtain a precursor colloidal solution by stirring; inject the colloidal solution into a pre-cooled mold to freeze-form, and prepare porous lithium manganate by freeze-drying, pre-oxidation and high-temperature sintering; The preparation method of the precursor colloidal solution is as follows: in parts by weight, dissolve 100 parts by weight of lithium acetate and 190 parts by weight of manganese acetate in anhydrous ethanol, and control the volume of ethanol to the total metal salt mass ratio to be 10mL / g; control the oxygen content to be ≤50ppm under a nitrogen atmosphere, and continue mixing at a mechanical stirring rate of 300rpm for 20min to form a uniform and transparent metal salt ethanol solution; then add 30 parts of 3.0wt.% acetone solution of polymethyl methacrylate dropwise to the above-mentioned metal salt ethanol solution at a rate of 1.0mL / min, control the system temperature to be maintained at 20°C during the dropwise addition, and continue stirring at a rate of 200rpm for 40min after the dropwise addition is completed to obtain A stable dispersed precursor colloid solution; the steps of freezing molding and freeze drying are as follows: injecting the precursor colloid solution into a metal copper mold pre-cooled to -50°C, wherein the microchannel width of the mold is 50μm and the depth is 200μm, and the inner surface is pre-coated with a polytetrafluoroethylene emulsion with a solid content of 10wt%, the coating thickness is 10μm, and the microchannel spacing is 1.0mm; gradient freezing is performed at a cooling rate of 2°C / min to form a frozen green body with a directional pore structure; then the frozen green body is transferred to a freeze dryer, and solvent sublimation is performed for 24 hours under the conditions of vacuum degree ≤5Pa and cold trap temperature ≤-85°C, and the residual solvent content is ≤0.5wt%, to obtain a dry green body. The steps of pre-oxidation and high-temperature sintering are as follows: the dried green body is then placed in a muffle furnace, the flow rate is controlled to 1L / min in an air atmosphere, and the temperature is increased to 350°C at a heating rate of 3°C / min, and the temperature is kept for 2.0 hours to complete the decomposition of the pore-forming agent and the oxidation of the precursor. The pre-oxidized green body is then placed in an alumina crucible, the flow rate is controlled to 1.0L / min in a flowing air atmosphere, and the temperature is increased to 700°C at a heating rate of 5°C / min, and the temperature is kept for 2 hours; after sintering, it is slowly cooled to room temperature at a rate of 5°C / min to obtain porous lithium manganate.

[0025] S2. The lithium triborate precursor solution is infiltrated into the pores of the porous substrate by vacuum-assisted impregnation, and subjected to gradient drying and annealing to form a lithium triborate-coated composite positive electrode material. The preparation method of the lithium triborate precursor solution is as follows: boric acid and lithium hydroxide are dissolved in deionized water at a molar ratio of 1:0.33, the pH of the solution is adjusted to 6.5, and the total boron ion concentration is controlled to be 0.5 mol / L; stirring at 200 rpm for 30 minutes at 25°C to form a transparent and homogeneous lithium triborate precursor solution. The impregnation process is as follows: immerse the porous lithium manganate of step S1 into the lithium triborate precursor solution, and keep it at a vacuum degree of 10kPa for 10min to achieve full penetration of the solution into the pores; then apply ultrasonic treatment, set the frequency to 20kHz, the power to 50W, and the time to 10min, and then use nitrogen pressure impregnation, the pressure is 0.5MPa, and the pressurization time is 10min to promote the uniform distribution of the sol; after the impregnation is completed, 0.5MPa nitrogen is used to purge the residual droplets on the surface to ensure that there is no excess solution accumulation in the pores. The gradient drying process includes: placing the impregnated material in a program temperature controlled drying oven and drying it in three stages: the first stage is dried at 25°C and humidity 30%RH for 1h; the second stage is dried at 60°C and humidity ≤10%RH for 2h; the third stage is dried at 100°C and vacuum degree ≤1kPa for 1h to complete the precursor dehydration and pre-crystallization. The annealing treatment includes: placing the dried material in a tubular furnace and annealing in a nitrogen-oxygen mixed atmosphere, wherein the volume ratio of nitrogen to oxygen is 97:3; the flow rate is 0.5L / min, heating to 300°C at 2°C / min and keeping warm for 1h; continuing to heat to 400°C at 3°C / min and keeping warm for 3h; finally cooling to room temperature at 2°C / min to obtain a lithium triborate-coated lithium manganate positive electrode material.

[0026] Figure 1 The morphological characteristics of the porous lithium manganese oxide prepared in Example 1 of the present invention are shown, and the interconnected columnar pore structure can be clearly observed, which proves that the material has good pore connectivity and is helpful to improve the lithium ion transmission rate. Figure 2 The morphology of the lithium triborate-coated lithium manganese oxide positive electrode material prepared in Example 1 is shown. Compared with the uncoated material, the overall structure remains intact without obvious collapse, proving that the coating process will not destroy the original pore structure. Figure 3 The cross-sectional microstructure morphology of the material was further characterized, and it was observed that the lithium triborate layer was evenly distributed on the surface of the lithium manganate, and the coating layer was continuous without obvious cracks, indicating that the coating process was stable and reliable. Figure 4 The XRD phase analysis results of the porous lithium manganate and lithium triborate coated lithium manganate positive electrode materials prepared in Example 1 of the present invention show good physical matching and no impurity phase peaks are detected, which proves that the material maintains its original crystal structure during the coating process.

[0027] Example 2 Lithium triborate coated lithium manganate positive electrode material; the positive electrode material is a porous lithium manganate / lithium triborate composite electrode material; the porous lithium manganate / lithium triborate composite electrode material includes porous lithium manganate and a lithium triborate coating coated on the pore surface of the porous lithium manganate; the mass ratio of porous lithium manganate to lithium triborate is 88.0:12.0; the porous lithium manganate has a highly connected directional columnar pore structure; the average diameter of the columnar pores of the porous lithium manganate is 60μm; the porosity of the porous lithium manganate is 69%; the thickness of the lithium triborate coating is 660nm.

[0028] A method for preparing a lithium triborate-coated lithium manganate positive electrode material in this embodiment comprises the following steps: S1. Dissolve lithium acetate and manganese acetate in anhydrous ethanol to form a metal salt solution, add an acetone solution of polymethyl methacrylate, and obtain a precursor colloidal solution by stirring; inject the colloidal solution into a pre-cooled mold to freeze-form, and prepare porous lithium manganate by freeze-drying, pre-oxidation and high-temperature sintering; The preparation method of the precursor colloidal solution is as follows: in parts by weight, 100 parts by weight of lithium acetate and 193 parts by weight of manganese acetate are dissolved in anhydrous ethanol, and the volume of ethanol and the mass ratio of the total metal salt are controlled to be 13mL / g; under a nitrogen atmosphere, the oxygen content is controlled to be ≤50ppm, and the mechanical stirring rate is 360rpm for continuous mixing for 23min to form a uniform and transparent metal salt ethanol solution; then 35 parts of 3.6wt.% polymethyl methacrylate acetone solution are added dropwise to the above-mentioned metal salt ethanol solution at a rate of 1.3mL / min, and the system temperature is controlled to be maintained at 22°C during the dropwise addition process. After the dropwise addition is completed, stirring is continued at a rate of 230rpm for 46min to obtain A stable dispersed precursor colloid solution; the steps of freeze molding and freeze drying are as follows: inject the precursor colloid solution into a metal copper mold pre-cooled to -47°C, the microchannel width of the mold is 65μm, the depth is 230μm, the inner surface is pre-coated with a polytetrafluoroethylene emulsion with a solid content of 12wt%, the coating thickness is 13μm, and the microchannel spacing is 1.3mm; gradient freezing is performed at a cooling rate of 2°C / min to form a frozen green body with a directional pore structure; then the frozen green body is transferred to a freeze dryer, and solvent sublimation is performed for 28 hours under the conditions of vacuum degree ≤5Pa and cold trap temperature ≤-85°C, and the residual solvent content is ≤0.5wt%, to obtain a dry green body. The steps of pre-oxidation and high-temperature sintering are as follows: the dried green body is then placed in a muffle furnace, the flow rate is controlled to 1L / min in an air atmosphere, and the temperature is increased to 359°C at a heating rate of 4°C / min, and the temperature is kept for 2.2 hours to complete the decomposition of the pore-forming agent and the oxidation of the precursor. The pre-oxidized green body is then placed in an alumina crucible, the flow rate is controlled to 1.2L / min in a flowing air atmosphere, and the temperature is increased to 706°C at a heating rate of 5°C / min, and the temperature is kept for 3 hours; after sintering, it is slowly cooled to room temperature at a rate of 6°C / min to obtain porous lithium manganate.

[0029] S2. The lithium triborate precursor solution is infiltrated into the pores of the porous substrate by vacuum-assisted impregnation, and subjected to gradient drying and annealing to form a lithium triborate-coated composite positive electrode material. The preparation method of the lithium triborate precursor solution is as follows: boric acid and lithium hydroxide are dissolved in deionized water at a molar ratio of 1:0.34, the pH of the solution is adjusted to 6.8, and the total boron ion concentration is controlled to be 0.8 mol / L; stirring at 260 rpm for 39 minutes at 30°C to form a transparent and homogeneous lithium triborate precursor solution. The impregnation process is as follows: immerse the porous lithium manganese oxide in step S1 into the lithium triborate precursor solution, and keep it at a vacuum degree of 16kPa for 16 minutes to achieve full penetration of the solution into the pores; then apply ultrasonic treatment, set the frequency to 26kHz, the power to 80W, and the time to 16 minutes, and then use nitrogen pressure impregnation, the pressure is 0.7MPa, and the pressurization time is 12 minutes to promote the uniform distribution of the sol; after the impregnation is completed, 0.7MPa nitrogen is used to purge the residual droplets on the surface to ensure that there is no excess solution accumulation in the pores. The gradient drying process includes: placing the impregnated material in a program temperature controlled drying oven and drying it in three stages: the first stage is dried at 30°C and humidity 36%RH for 1 hour; the second stage is dried at 66°C and humidity ≤10%RH for 3 hours; the third stage is dried at 106°C and vacuum degree ≤1kPa for 1 hour to complete the precursor dehydration and pre-crystallization. The annealing treatment includes: placing the dried material in a tubular furnace and annealing in a nitrogen-oxygen mixed atmosphere, wherein the volume ratio of nitrogen to oxygen is 96:4; the flow rate is 0.8L / min, heating to 330°C at 3°C / min and keeping warm for 1h; continuing to heat to 430°C at 5°C / min and keeping warm for 4h; finally cooling to room temperature at 5°C / min to obtain a lithium triborate-coated lithium manganate positive electrode material.

[0030] Example 3 Lithium triborate coated lithium manganate positive electrode material; the positive electrode material is a porous lithium manganate / lithium triborate composite electrode material; the porous lithium manganate / lithium triborate composite electrode material includes porous lithium manganate and a lithium triborate coating coated on the pore surface of the porous lithium manganate; the mass ratio of porous lithium manganate to lithium triborate is 90.0:10.0; the porous lithium manganate has a highly connected directional columnar pore structure; the average diameter of the columnar pores of the porous lithium manganate is 75μm; the porosity of the porous lithium manganate is 73%; the thickness of the lithium triborate coating is 720nm.

[0031] A method for preparing a lithium triborate-coated lithium manganate positive electrode material in this embodiment comprises the following steps: S1. Dissolve lithium acetate and manganese acetate in anhydrous ethanol to form a metal salt solution, add an acetone solution of polymethyl methacrylate, and obtain a precursor colloidal solution by stirring; inject the colloidal solution into a pre-cooled mold to freeze-form, and prepare porous lithium manganate by freeze-drying, pre-oxidation and high-temperature sintering; The preparation method of the precursor colloidal solution is as follows: in parts by weight, dissolve 100 parts by weight of lithium acetate and 196 parts by weight of manganese acetate in anhydrous ethanol, and control the volume of ethanol to the total metal salt mass ratio to be 16mL / g; control the oxygen content to be ≤50ppm under a nitrogen atmosphere, and continue mixing at a mechanical stirring rate of 420rpm for 26min to form a uniform and transparent metal salt ethanol solution; then add 39 parts of 4.2wt.% polymethyl methacrylate in acetone solution dropwise at a rate of 1.6mL / min to the above-mentioned metal salt ethanol solution, control the system temperature to be maintained at 23°C during the dropwise addition, and continue stirring at a rate of 260rpm for 52min after the dropwise addition is completed to obtain A stable dispersed precursor colloidal solution; the steps of freeze molding and freeze drying are as follows: injecting the precursor colloidal solution into a metal copper mold precooled to -44°C, wherein the microchannel width of the mold is 80 μm and the depth is 260 μm, and the inner surface is pre-coated with a polytetrafluoroethylene emulsion with a solid content of 13wt%, the coating thickness is 16 μm, and the microchannel spacing is 1.6 mm; gradient freezing is performed at a cooling rate of 3°C / min to form a frozen green body with a directional pore structure; then the frozen green body is transferred to a freeze dryer, and solvent sublimation is performed for 31 hours under the conditions of a vacuum degree of ≤5Pa and a cold trap temperature of ≤-85°C, and the residual solvent content is ≤0.5wt%, to obtain a dry green body. The steps of pre-oxidation and high-temperature sintering are as follows: the dried green body is then placed in a muffle furnace, the flow rate is controlled to 2L / min in an air atmosphere, and the temperature is increased to 368°C at a heating rate of 4°C / min, and the temperature is kept for 2.3 hours to complete the decomposition of the pore-forming agent and the oxidation of the precursor. The pre-oxidized green body is then placed in an alumina crucible, the flow rate is controlled to 1.3L / min in a flowing air atmosphere, and the temperature is increased to 712°C at a heating rate of 6°C / min, and the temperature is kept for 3 hours; after sintering, it is slowly cooled to room temperature at a rate of 7°C / min to obtain porous lithium manganese oxide.

[0032] S2. The lithium triborate precursor solution is infiltrated into the pores of the porous substrate by vacuum-assisted impregnation, and subjected to gradient drying and annealing to form a lithium triborate-coated composite positive electrode material. The preparation method of the lithium triborate precursor solution is as follows: boric acid and lithium hydroxide are dissolved in deionized water at a molar ratio of 1:0.34, the pH of the solution is adjusted to 7.1, and the total boron ion concentration is controlled to be 1.1 mol / L; stirring at 320 rpm for 48 minutes at 34°C to form a transparent and homogeneous lithium triborate precursor solution. The impregnation process is as follows: immerse the porous lithium manganate of step S1 into the lithium triborate precursor solution, and keep it at a vacuum of 22kPa for 22min to achieve full penetration of the solution into the pores; then apply ultrasonic treatment, set the frequency to 32kHz, the power to 110W, and the time to 22min, and then use nitrogen pressure impregnation, the pressure is 0.8MPa, and the pressurization time is 13min to promote the uniform distribution of the sol; after the impregnation is completed, purge the residual droplets on the surface with 0.8MPa nitrogen to ensure that there is no excess solution accumulation in the pores. The gradient drying process includes: placing the impregnated material in a program temperature controlled drying oven and drying it in three stages: the first stage is dried at 34°C and 42%RH for 2h; the second stage is dried at 72°C and ≤10%RH for 3h; the third stage is dried at 112°C and ≤1kPa for 2h to complete the precursor dehydration and pre-crystallization. The annealing treatment includes: placing the dried material in a tubular furnace and annealing in a nitrogen-oxygen mixed atmosphere, wherein the volume ratio of nitrogen to oxygen is 95:5; the flow rate is 1.1 L / min, heating to 360°C at 4°C / min and keeping warm for 2 hours; continuing to heat to 460°C at 6°C / min and keeping warm for 4 hours; finally cooling to room temperature at 7°C / min to obtain a lithium triborate-coated lithium manganate positive electrode material.

[0033] Example 4 Lithium triborate coated lithium manganate positive electrode material; the positive electrode material is a porous lithium manganate / lithium triborate composite electrode material; the porous lithium manganate / lithium triborate composite electrode material includes porous lithium manganate and a lithium triborate coating coated on the pore surface of the porous lithium manganate; the mass ratio of porous lithium manganate to lithium triborate is 92.0:8.0; the porous lithium manganate has a highly connected directional columnar pore structure; the average diameter of the columnar pores of the porous lithium manganate is 95μm; the porosity of the porous lithium manganate is 78%; the thickness of the lithium triborate coating is 800nm.

[0034] A method for preparing a lithium triborate-coated lithium manganate positive electrode material in this embodiment comprises the following steps: S1. Dissolve lithium acetate and manganese acetate in anhydrous ethanol to form a metal salt solution, add an acetone solution of polymethyl methacrylate, and obtain a precursor colloidal solution by stirring; inject the colloidal solution into a pre-cooled mold to freeze-form, and prepare porous lithium manganate by freeze-drying, pre-oxidation and high-temperature sintering; The preparation method of the precursor colloidal solution is as follows: in parts by weight, 100 parts by weight of lithium acetate and 200 parts by weight of manganese acetate are dissolved in anhydrous ethanol, and the volume of ethanol and the mass ratio of the total metal salt are controlled to be 20mL / g; under a nitrogen atmosphere, the oxygen content is controlled to be ≤50ppm, and the mechanical stirring rate is 500rpm for continuous mixing for 30min to form a uniform and transparent metal salt ethanol solution; then 45 parts of 5.0wt.% polymethyl methacrylate acetone solution are added dropwise to the above-mentioned metal salt ethanol solution at a rate of 2.0mL / min, and the system temperature is controlled to be maintained at 25°C during the dropwise addition process. After the dropwise addition is completed, stirring is continued at a rate of 300rpm for 60min to obtain a separation. The steps of freeze forming and freeze drying are as follows: injecting the precursor colloidal solution into a metal copper mold precooled to -40°C, wherein the microchannel width of the mold is 100 μm and the depth is 300 μm, and the inner surface is pre-coated with a polytetrafluoroethylene emulsion with a solid content of 15wt%, the coating thickness is 20 μm, and the microchannel spacing is 2.0 mm; gradient freezing is performed at a cooling rate of 3°C / min to form a frozen green body with a directional pore structure; then the frozen green body is transferred to a freeze dryer, and solvent sublimation is performed for 36 hours under the conditions of vacuum degree ≤5Pa and cold trap temperature ≤-85°C, and the residual solvent content is ≤0.5wt%, thereby obtaining a dried green body. The steps of pre-oxidation and high-temperature sintering are as follows: the dried green body is then placed in a muffle furnace, the flow rate is controlled to 2L / min in an air atmosphere, and the temperature is increased to 380°C at a heating rate of 5°C / min, and the temperature is kept for 2.5 hours to complete the decomposition of the pore-forming agent and the oxidation of the precursor. The pre-oxidized green body is then placed in an alumina crucible, the flow rate is controlled to 1.5L / min in a flowing air atmosphere, and the temperature is increased to 720°C at a heating rate of 6°C / min, and the temperature is kept for 4 hours; after sintering, it is slowly cooled to room temperature at a rate of 8°C / min to obtain porous lithium manganate.

[0035] S2. The lithium triborate precursor solution is infiltrated into the pores of the porous substrate by vacuum-assisted impregnation, and subjected to gradient drying and annealing to form a lithium triborate-coated composite positive electrode material. The preparation method of the lithium triborate precursor solution is as follows: boric acid and lithium hydroxide are dissolved in deionized water at a molar ratio of 1:0.35, the pH of the solution is adjusted to 7.5, and the total boron ion concentration is controlled to be 1.5 mol / L; stirring at 400 rpm for 60 min at 40°C to form a transparent and homogeneous lithium triborate precursor solution. The impregnation process is as follows: immerse the porous lithium manganate of step S1 into the lithium triborate precursor solution, and keep it at a vacuum degree of 30kPa for 30min to achieve full penetration of the solution into the pores; then apply ultrasonic treatment, set the frequency to 40kHz, the power to 150W, and the time to 30min, and then use nitrogen pressure impregnation, the pressure is 1.0MPa, and the pressurization time is 15min to promote the uniform distribution of the sol; after the impregnation is completed, purge the residual droplets on the surface with 1.0MPa nitrogen to ensure that there is no excess solution accumulation in the pores. The gradient drying process includes: placing the impregnated material in a program temperature controlled drying oven and drying it in three stages: the first stage is dried at 40°C and 50%RH for 2h; the second stage is dried at 80°C and ≤10%RH for 4h; the third stage is dried at 120°C and ≤1kPa for 2h to complete the precursor dehydration and pre-crystallization. The annealing treatment includes: placing the dried material in a tubular furnace and annealing in a nitrogen-oxygen mixed atmosphere, wherein the volume ratio of nitrogen to oxygen is 93:7; the flow rate is 1.5L / min, heating to 400°C at 5°C / min and keeping warm for 2h; continuing to heat to 500°C at 8°C / min and keeping warm for 5h; finally cooling to room temperature at 10°C / min to obtain a lithium triborate-coated lithium manganate positive electrode material.

[0036] Figure 5 The cross-sectional microstructure of the lithium triborate-coated lithium manganate positive electrode material prepared in Example 4 of the present invention is further verified. The results also show that the lithium triborate layer is uniformly coated, further proving the feasibility and stability of the process of the present invention. In summary, these experimental results jointly confirm the superiority of the lithium triborate-coated porous lithium manganate positive electrode material prepared by the present invention in terms of microstructure, phase retention and coating uniformity.

[0037] Comparative Example 1 It is basically the same as Example 1, except that the mold is not pre-cooled during freeze molding, resulting in uneven pore structure and reduced pore connectivity.

[0038] Comparative Example 2 The method is basically the same as Example 1, except that the volume ratio of ethanol to the total metal salt mass is set to 5 mL / g.

[0039] Comparative Example 3 Basically the same as in Example 1, the freezing process in step S1 is performed at a gradient freezing rate of 5°C / min.

[0040] Comparative Example 4 It is basically the same as Example 1, except that vacuum-assisted impregnation is not performed, resulting in the lithium triborate precursor solution being unable to fully penetrate into the pores.

[0041] Comparative Example 5 It is basically the same as Example 1, except that the mold is not pre-cooled during freeze molding, resulting in uneven pore structure and reduced pore connectivity.

[0042] Comparative Example 6 It is basically the same as Example 1, except that the ultrasonic treatment frequency is set to 10 kHz, which is lower than the standard range of the example, resulting in uneven distribution of the sol in the pores and too thin local coating layer, affecting the long-cycle stability.

[0043] Comparative Example 7 It is basically the same as Example 1, except that the nitrogen pressure impregnation step is cancelled, resulting in uneven thickness distribution of the lithium triborate coating layer, and an overly thick layer is formed in some areas, which affects the diffusion rate of lithium ions.

[0044] Comparative Example 8 It is basically the same as Example 1, except that the heating rate of high-temperature sintering is set to 8°C / min instead of 5°C / min, which causes the grains to grow too fast during the sintering process, the pore structure to collapse, and the specific capacity of the material to decrease.

[0045] Comparative Example 9 It is basically the same as Example 1, except that the thickness of the lithium triborate coating is set to 500 nm, which is lower than the standard range, resulting in insufficient protection of the coating layer and reduced resistance to manganese dissolution of the material.

[0046] Comparative Example 10 It is basically the same as Example 3, except that the high-temperature sintering temperature is set to 750°C, which is higher than the standard range, resulting in lithium manganese oxide lattice distortion and shortened cycle life of the electrode material.

[0047] Performance Test: Electrochemical cycle stability test: In order to evaluate the long-cycle stability of lithium triborate-coated porous lithium manganese oxide cathode materials, CR2032 button cells (half-cell, with metal lithium as the counter electrode) and full cells (matched with graphite anode, strictly controlling the anode / cathode capacity ratio N / P=1.1–1.2) were used for electrochemical tests. The electrolyte used was a conventional 1M LiPF6 dissolved in a mixed solvent system of EC:DMC (1:1 volume ratio), and the test temperatures were set at 25°C and 55°C, respectively. Constant current charge and discharge cycles were performed at 0.1C and 1C rates, with a voltage range of 3.0–4.3 V (half-cell) and 2.8–4.2 V (full cell), and the charge and discharge curves were recorded at the 1st, 10th, 25th, 50th, 75th, and 100th cycles, respectively, and the capacity retention rate and coulombic efficiency were calculated. The change trend of polarization voltage was analyzed to comprehensively evaluate the cycle stability of the material under different temperature and rate conditions.

[0048] Rate performance and impedance analysis: In order to further study the effect of lithium triborate coating on the rate performance and charge transfer dynamics of the positive electrode material, a CR2032 half-cell system was first used to perform constant current charge and discharge tests at 0.1C, 0.5C, 1C, 2C, and 5C at 25°C, and the rate-capacity relationship curve was drawn. After the rate test, the battery was cycled 5 times at a rate of 0.5C and left to stand for 2 hours after the discharge to reach a stable state. Then, an electrochemical impedance spectroscopy (EIS) analysis was performed, with the frequency scan range set to 10 mHz–100 kHz and the AC signal amplitude set to 5 mV. The impedance data was fitted using ZView software to accurately extract the charge transfer impedance (R ct ) and other kinetic parameters. In addition, the constant current intermittent titration technique (GITT) was used to charge and discharge at a C / 20 rate, and the change of the open circuit voltage between each step with time was recorded in real time, and the lithium ion diffusion coefficient (D-Li⁺) was calculated to quantitatively analyze the correlation between the rate performance of the material and the internal ion diffusion kinetics. .

[0049] Dynamic anti-manganese dissolution test: In order to systematically evaluate the inhibitory effect of lithium triborate coating on manganese dissolution in lithium manganate positive electrode materials, multiple parallel batteries (CR2032 button half-cells) were assembled, and the batteries were disassembled after 10, 50, and 100 cycles at 1C rate at 60°C. The electrolyte was collected, and the concentration of dissolved Mn²⁺ in the electrolyte was determined by inductively coupled plasma optical emission spectrometry (ICP-OES), and the dynamic evolution trend of manganese dissolution was analyzed. At the same time, the positive electrode material after the corresponding cycle was taken out, and the chemical valence distribution of Mn element on the positive electrode surface was analyzed by X-ray photoelectron spectroscopy (XPS) to clarify the inhibitory mechanism of coating on manganese ion dissolution. In addition, synchrotron radiation X-ray diffraction technology (in situ XRD) was used to track the changes in lattice parameters of the material during the charge and discharge cycle in real time, and to monitor the evolution of LiMn2O4 crystal structure with the number of cycles, so as to explore the mechanism of lithium triborate coating on Jahn-Teller distortion and manganese dissolution behavior.

[0050] The properties of the positive electrode materials of Examples 1 to 4 and Comparative Examples 1 to 10 are summarized in Table 1.

[0051] Table 1 Performance of positive electrode materials of Examples 1 to 4 and Comparative Examples 1 to 10

[0052] As can be seen from Table 1, a sintering temperature that is too high may cause the lithium manganese oxide lattice distortion and affect the cycle stability, but at the same time it may increase the crystallinity of the material, reduce the interfacial impedance in the short term, and make the initial capacity retention rate higher. A heating rate that is too fast may cause abnormal grain growth and collapse of the pore structure, thereby reducing the rate performance and cycle stability. If the mold is not pre-cooled or the cooling rate is unreasonable during the freeze molding process, it may lead to uneven pore structure, reduced pore connectivity, and affect the lithium ion diffusion rate, thereby reducing the rate performance and cycle life. An improper ratio of ethanol volume to metal salt may affect the uniformity of the sol, resulting in uneven distribution of the coating thickness, thereby affecting the rate performance and impedance characteristics. If vacuum-assisted impregnation or nitrogen pressure impregnation is not performed, the lithium triborate precursor solution may not be able to fully penetrate into the pores, resulting in the coating layer being too thin or too thick locally, affecting the resistance to manganese dissolution and charge transfer impedance. Too low an ultrasonic treatment frequency may cause the sol to be unevenly distributed in the pores and the local coating layer to be too thin, thereby affecting long-term cycle stability. Improper heating rate or temperature control during high-temperature sintering may lead to excessively fast grain growth, pore collapse, and reduced material specific capacity, while exacerbating Jahn-Teller distortion and increasing manganese dissolution. In addition, if the coating is too thin, it may not be able to effectively inhibit manganese dissolution, while if it is too thick, it may hinder lithium ion diffusion and affect rate performance.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. Lithium triborate coated lithium manganate positive electrode material, characterized in that: The positive electrode material is a porous lithium manganate / lithium triborate composite electrode material; The porous lithium manganate / lithium triborate composite electrode material comprises porous lithium manganate and a lithium triborate coating coated on the pore surface of the porous lithium manganate; The mass ratio of the porous lithium manganese oxide to lithium triborate is (86.0-92.0): (8.0-14.0); The porous lithium manganese oxide is a highly connected directional columnar pore structure; The average diameter of the columnar pores of the porous lithium manganese oxide is 45-95 μm; The porosity of the porous lithium manganese oxide is 65-78%; The thickness of the lithium triborate coating is 600-800 nm.

2. A method for preparing the lithium triborate-coated lithium manganate positive electrode material as claimed in claim 1, characterized in that: The following steps are involved: S1. dissolving lithium acetate and manganese acetate in anhydrous ethanol to form a metal salt solution, adding an acetone solution of polymethyl methacrylate, and stirring to obtain a precursor colloidal solution; The colloidal solution is injected into a pre-cooled mold to freeze and form, and porous lithium manganese oxide is prepared by freeze drying, pre-oxidation and high-temperature sintering; S2. The lithium triborate precursor solution is infiltrated into the pores of the porous substrate by vacuum-assisted impregnation, and then subjected to gradient drying and annealing to form a lithium triborate-coated composite positive electrode material.

3. The method for preparing a lithium triborate-coated lithium manganate positive electrode material according to claim 2, characterized in that: The preparation method of the precursor colloidal solution in step S1 is as follows: by weight, 100 parts by weight of lithium acetate and 190-200 parts by weight of manganese acetate are dissolved in anhydrous ethanol, and the volume ratio of ethanol to the total mass of metal salt is controlled to be 10-20 mL / g; under a nitrogen atmosphere, the oxygen content is controlled to be ≤50 ppm, and the mixture is continuously mixed at a mechanical stirring rate of 300-500 rpm for 20-30 min to form a uniform and transparent metal salt ethanol solution; then 30-45 parts of 3.0-5.0 wt.% polymethyl methacrylate acetone solution are dropwise added to the above metal salt ethanol solution at a rate of 1.0-2.0 mL / min, and the system temperature is controlled to be maintained at 20-25° C. during the dropping process. After the dropping is completed, stirring is continued at a rate of 200-300 rpm for 40-60 min to obtain a dispersed and stable precursor colloidal solution.

4. The method for preparing a lithium triborate-coated lithium manganate positive electrode material according to claim 2, characterized in that The steps of freeze forming and freeze drying in step S1 are as follows: injecting the precursor colloidal solution into a metal copper mold precooled to -50~-40°C, wherein the microchannel width of the mold is 50~100μm and the depth is 200~300μm, and the inner surface is pre-coated with a polytetrafluoroethylene emulsion with a solid content of 10~15wt%, the coating thickness is 10~20μm, and the microchannel spacing is 1.0~2.0mm; gradient freezing is performed at a cooling rate of 2~3°C / min to form a frozen body with a directional pore structure; then the frozen body is transferred to a freeze dryer, and solvent sublimation is performed for 24~36h under the conditions of vacuum degree ≤5Pa and cold trap temperature ≤-85°C, and the residual solvent content is ≤0.5wt%, to obtain a dried body.

5. The method for preparing a lithium triborate-coated lithium manganate positive electrode material according to claim 2, characterized in that: The steps of pre-oxidation and high-temperature sintering in step S1 are as follows: then placing the dried green body in a muffle furnace, controlling the flow rate to 1-2 L / min in an air atmosphere, heating to 350-380°C at a heating rate of 3-5°C / min, and keeping warm for 2.0-2.5 hours to complete the decomposition of the pore-forming agent and the oxidation of the precursor, then placing the pre-oxidized green body in an alumina crucible, controlling the flow rate to 1.0-1.5 L / min in a flowing air atmosphere, heating to 700-720°C at a heating rate of 5-6°C / min, and keeping warm for 2-4 hours; after sintering, slowly cooling to room temperature at a rate of 5-8°C / min to obtain porous lithium manganate.

6. The method for preparing a lithium triborate-coated lithium manganate positive electrode material according to claim 2, characterized in that: The preparation method of the lithium triborate precursor solution in step S2 is as follows: dissolve boric acid and lithium hydroxide in deionized water at a molar ratio of 1:(0.33-0.35), adjust the solution pH to 6.5-7.5, and control the total boron ion concentration to 0.5-1.5 mol / L; stir at 200-400 rpm for 30-60 min at 25-40° C. to form a transparent and homogeneous lithium triborate precursor solution.

7. The method for preparing a lithium triborate-coated lithium manganate positive electrode material according to claim 2, characterized in that: The impregnation process in step S2 is as follows: immersing the porous lithium manganate in step S1 into the lithium triborate precursor solution, maintaining the vacuum degree of 10-30 kPa for 10-30 min to achieve sufficient penetration of the solution into the pores; then applying ultrasonic treatment, setting the frequency to 20-40 kHz, the power to 50-150 W, and the time to 10-30 min, and then using nitrogen pressure impregnation with a pressure of 0.5-1.0 MPa and a pressurization time of 10-15 min to promote uniform distribution of the sol; after the impregnation is completed, 0.5-1.0 MPa nitrogen is used to purge the residual droplets on the surface to ensure that there is no excessive solution accumulation in the pores.

8. The method for preparing a lithium triborate-coated lithium manganate positive electrode material according to claim 2, characterized in that: The gradient drying process in step S2 includes: placing the impregnated material in a program-controlled temperature drying oven and drying it in three stages: the first stage is drying at 25-40°C and humidity 30-50%RH for 1-2 hours; the second stage is drying at 60-80°C and humidity ≤10%RH for 2-4 hours; the third stage is drying at 100-120°C and vacuum ≤1kPa for 1-2 hours to complete the dehydration and pre-crystallization of the precursor.

9. The method for preparing a lithium triborate-coated lithium manganate positive electrode material according to claim 2, characterized in that: The annealing treatment in step S2 includes: placing the dried material in a tubular furnace and annealing in a nitrogen-oxygen mixed atmosphere, wherein the volume ratio of nitrogen to oxygen is (93~97):(3~7); the flow rate is 0.5~1.5L / min, heating to 300~400°C at 2~5°C / min and keeping warm for 1~2h; continuing to heat to 400~500°C at 3~8°C / min and keeping warm for 3~5h; finally cooling to room temperature at 2~10°C / min to obtain a lithium triborate-coated lithium manganate positive electrode material.

Citation Information

Patent Citations

  • Lithium manganese iron phosphate coated lithium manganate positive electrode material and preparation method thereof

    CN118908285A

  • AnodePositive electrode material of lithium ion battery with porous laminated structure and preparation method thereof

    CN102956883A

  • Nickel-cobalt-lithium manganese positive electrode material with boron-lithium composite oxide clad on surface, and preparation method thereof

    CN103236521A

  • Porous metallic cathode material doped with lithium manganate / carbon for composite lithium batteries, and preparation method of porous metallic cathode material

    CN104795557A

  • Positive electrode material precursor and preparation method and application thereof

    CN118255398A